Knockout of mafba Causes Inner-Ear Developmental Defects in Zebrafish via the Impairment of Proliferation and Differentiation of Ionocyte Progenitor Cells - Xiang Chen; Yuwen Huang; Pan Gao; Yuexia Lv; Danna Jia; Kui Sun; Yunqiao Han; Hualei Hu; Zhaohui Tang; Xiang Ren; Mugen Liu (Biomedicines, 2021)
Zebrafish is an excellent model for exploring the development of the inner ear. Its inner ear has similar functions to that of humans, specifically in the maintenance of hearing and balance. Mafba is a component of the Maf transcription factor family. It participates in multiple biological processes, but its role in inner-ear development remains poorly understood. In this study, we constructed a mafba knockout (mafba−/−) zebrafish model using CRISPR/Cas9 technology. The mafba−/− mutant inner ear displayed severe impairments, such as enlarged otocysts, smaller or absent otoliths, and insensitivity to sound stimulation. The proliferation of p63+ epidermal stem cells and dlc+ ionocyte progenitors was inhibited in mafba−/− mutants. Moreover, the results showed that mafba deletion induces the apoptosis of differentiated K+-ATPase-rich (NR) cells and H+-ATPase-rich (HR) cells. The activation of p53 apoptosis and G0/G1 cell cycle arrest resulted from DNA damage in the inner-ear region, providing a mechanism to account for the inner ear deficiencies. The loss of homeostasis resulting from disorders of ionocyte progenitors resulted in structural defects in the inner ear and, consequently, loss of hearing. In conclusion, the present study elucidated the function of ionic channel homeostasis and inner-ear development using a zebrafish Mafba model and clarified the possible physiological roles.